2013
DOI: 10.7860/jcdr/2013/6912.3451
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yoga on Autonomic Functions and Psychological Status During Both Phases of Menstrual Cycle in Young Healthy Females

Abstract: Context: Premenstrual stress affects 75% of women of childbearing age and yoga has been found to be beneficial in many psycho-somatic disorders. Aims:To investigate the effect of integrated yoga on autonomic parameters and psychological well-being during both pre and post phases of menstrual cycle in healthy young female subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“… †P<0.05 between groups at follow-up. ‡(Kanojia et al (2013) 46 P<0.05 comparison between premenstrual and postmenstrual phase. §(Kanojia et al (2013) 46 P<0.05 in comparison with initial cycle.…”
Section: Methodsmentioning
confidence: 98%
“… †P<0.05 between groups at follow-up. ‡(Kanojia et al (2013) 46 P<0.05 comparison between premenstrual and postmenstrual phase. §(Kanojia et al (2013) 46 P<0.05 in comparison with initial cycle.…”
Section: Methodsmentioning
confidence: 98%
“…Based on the research by Kanojia et al (21), the number of the subjects to be involved in the study was calculated by considering 95% interval confidence and 80% of power for 26 cases for yoga group (-17.50 ± 12.43) and 26 cases for control group (-0.65 ± 27.54). A 20% dropout was considered in cases, so 31 subjects were calculated per group.…”
Section: Methodsmentioning
confidence: 99%
“…Physical activity is one coping strategy that is perhaps underutilized by many college students. [ 11 ] Many systematic reviews and different studies on effects on yoga for stress management in college students revealed positive effects of yoga (as a mind-body intervention) on stress reduction in college student. [ 12 13 14 ]…”
Section: Yogamentioning
confidence: 99%
“…Based on clinical management and psychophysiological effects of yoga in college students, the suggested evidence-based yoga therapy for college students may include following yogic practices:[ 11 13 16 17 18 23 24 ]…”
Section: Yogamentioning
confidence: 99%